2021
DOI: 10.1177/07067437211044717
|View full text |Cite
|
Sign up to set email alerts
|

Youth Perspectives on Integrated Youth Services: A Discrete Choice Conjoint Experiment

Abstract: Objective Integrated youth services (IYS) are an emerging model of care offering a broad range of mental health and social services for youth in one location. This study aimed to determine the IYS service characteristics most important to youth, as well as to determine whether different classes of youth have different service preferences, and if so, what defines these classes. Methods Ontario youth aged 14–29 years with mental health challenges were recruited to participate in a discrete choice experiment (DCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Such interventions cannot solely rely on the feedback and input of mental health professionals, advocates, and policymakers, but also equally benefit from engaging young people. Consistent with our study, the researchers suggested co-designing interventions with the youth in the target population [ 55 ]. The citiesRISE platform could play an instrumental role connecting young people and key stakeholders, establishing a systematic way to engage youth in shaping implementation of interventions in Seattle [ 17 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Such interventions cannot solely rely on the feedback and input of mental health professionals, advocates, and policymakers, but also equally benefit from engaging young people. Consistent with our study, the researchers suggested co-designing interventions with the youth in the target population [ 55 ]. The citiesRISE platform could play an instrumental role connecting young people and key stakeholders, establishing a systematic way to engage youth in shaping implementation of interventions in Seattle [ 17 ].…”
Section: Discussionsupporting
confidence: 83%
“…For instance, social and criminal justice actions such as reducing youth incarceration could change the trajectory of life for youth at risk for justice involvement and improve mental health in the long-term. A recent study on integrated youth services as an emerging model of care pointed to the need for flexible models of service delivery [ 55 ]. Such interventions cannot solely rely on the feedback and input of mental health professionals, advocates, and policymakers, but also equally benefit from engaging young people.…”
Section: Discussionmentioning
confidence: 99%
“…Data gathered from an Ontario-wide DCE has examined the IYS service preferences of youth, caregivers, and stakeholder groups [19][20][21]. Most relevant to the current data analysis are findings from the Hawke and colleagues [20] study examining the IYS service preferences of Ontario caregivers that found three caregiver latent classes.…”
Section: Using Discrete Choice Conjoint Methodology To Understand Ser...mentioning
confidence: 99%
“…They force participants to make trade-offs, identifying the importance of different service attributes [ 32 , 33 ]. Previous findings generated from DCE studies have been useful in informing service design and delivery, resource allocation, and policies, including the preferred design of IYS services [ 34 37 ].…”
Section: Introductionmentioning
confidence: 99%